36‐4: Solution‐Processed Transparent Top Electrode for QD‐LED. Issue 1 (25th September 2020) - Hopkin, Hywel T.; Boardman, Edward A.; Smeeton, Tim M.
Abstract : A solution‐processed transparent electrode has been developed for use as a top electrode in a top‐emitting electroluminescent QD‐LED. The top electrode comprises an ITO nanoparticle film and a wire grid auxiliary electrode and provides a low sheet resistance of 1.6 Ω sq −1 and a high transmission of over 93% for visible light.